Fiasco : - Parish, James Robert (John Wiley & Sons, 2006)
A longtime industry insider and acclaimed Hollywood historian goes behind the scenes to tell the stories of 15 of the most spectacular movie megaflops of the past 50 years, such as Cleopatra, The Cotton Club, and Waterworld. He recounts, in every gory detail, how enormous hubris, unbridled ambition, artistic hauteur, and bad business sense on the parts of Tinsel Town wheeler-dealers and superstars such as Elizabeth Taylor, Clint Eastwood, and Francis Ford Coppola, conspired to engender some of the worst films ever.